Antibacterial activities of Meloxicam, Ibuprofen and Diclofenac: an Additional Approach to their Immunological Therapy - Professor Ali Abdul Hussein S. AL-Janabi (Karbala Journal of Medicine, 2025)
Non-steroidal anti-inflammatory drugs (NSAIDs) are anti-inflammatory, antipyretic, and analgesic drugs that are frequently utilized in the treatment of musculoskeletal disorders, mild to moderate pain, and fever [1]. Such immunological activities are not the sole method by which NSAIDs can prevent diseases. They also have direct potential inhibitory effects on several types of organisms. Antibacterial activities of some NSAIDs have been observed against different pathogenic bacteria.